2001
DOI: 10.3748/wjg.v7.i5.735
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of rotaviral gastroenteritis with Qiwei Baizhu powder

Abstract: AIM To observe the effects of Qiwei Baizhu Powder (QWBZP) on rotaviral gastroenteritis in children and in animal models.METHODS Enrolled patients were divided into two groups, and one group was treated with oral rehydration solution (ORS) and the other treat ed with oral liquid of QWBZP. Neonate mice were orally infected with 50 µ µ µ µ µL rotavirus suspension (4×10 8 PFU/mL) and treated with ORS or oral liquid of QWBZP, respectively.RESULTS Eighty-three cases of rotaviral gastroenteritis treated with QWBZP re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The relief of diarrhoea in rotavirus infected piglets by lentinan administration may be the result of improved intestinal microbiota and attenuation of apoptosis (145). Animal tests of Qiwei Baizhu powder confirmed that the drug reduces pathological damage such as small intestinal mucosa and villi damage and improves small intestinal absorption (146). Oral administration of transforming growth factor alpha promotes the recovery of mucosal damage induced by rotavirus enteritis in pigs (147).…”
Section: Increasing Intestinal Barrier Functionmentioning
confidence: 99%
“…The relief of diarrhoea in rotavirus infected piglets by lentinan administration may be the result of improved intestinal microbiota and attenuation of apoptosis (145). Animal tests of Qiwei Baizhu powder confirmed that the drug reduces pathological damage such as small intestinal mucosa and villi damage and improves small intestinal absorption (146). Oral administration of transforming growth factor alpha promotes the recovery of mucosal damage induced by rotavirus enteritis in pigs (147).…”
Section: Increasing Intestinal Barrier Functionmentioning
confidence: 99%
“…Accumulating evidence indicates the usefulness of PWS in the treatment of common gastrointestinal disorders, such as gastritis, esophageal reflux, gastric or duodenal ulcers, and acute or chronic enteritis [43]. It has been revealed that RAM prevents virus-induced gastroenteritis via the protection of intestinal mucosal cells against injury and improvement in the absorption [44]. However, the effect of PWS on acute colitis has not yet been described in detail.…”
Section: Introductionmentioning
confidence: 99%